HER+: Harnessing gender and social equality for resilience in agrifood systems - CGIAR System Organization (CGIAR System Organization, 2022)
HER+ is a CGIAR research initiative working to achieve climate resilience by strengthening gender equality and social inclusion across food systems in the Global South.